Implementation of Marriage Agreements in Resolving Property Conflicts with Husband and Wife - Daud Nento, Fadel; Mashdurohatun, Anis (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze the implementation of marriage agreements in resolving joint property disputes between husband and wife at the Gorontalo Religious Court and identify obstacles and their solutions. The research method used is empirical legal research with a qualitative approach, through literature studies, observations, in-depth interviews with judges and clerks, and document analysis of 37 decisions in joint property cases in 2020–2024. The results of the study indicate that the implementation of marriage agreements is realized in the form of a peace deed through mediation, such as in Case Number 689/Pdt.G/2022/PA.Gtlo. However, its implementation is still low because the majority of cases are resolved through litigation with a 50:50 division based on Article 97 of the Compilation of Islamic Law, although there are two decisions that deviate from the proportional division (2/3 and 1/3) based on the wife's contribution. The main obstacles include: (1) legal structure, namely the less than optimal role of mediators and the dominance of the litigation process; (2) legal substance, namely general and unclear norms regarding marriage agreements; (3) legal culture, namely the taboo perception in Gorontalo society regarding marriage contracts. The solutions offered are optimizing mediation, prioritizing non-litigation resolution, improving legal norms, strengthening marriage contract norms, and socializing through local cultural channels such as the Tolobalango traditional procession. This study concludes that marriage contracts have the potential to be an effective preventive and resolutive instrument if supported by institutional strengthening, certainty of norms, and a paradigm shift in legal culture.